1987
DOI: 10.1139/y87-169
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of pH and Ca2+ in bloodstream and brain

Abstract: The highlights of the literature and our work on tetany and hyperventilation are reviewed. Our studies concern the following: (1) the changes of [Ca2+] in circulating plasma caused by respiratory and "metabolic" acidosis and alkalosis; (2) critical plasma [Ca2+] levels associated with signs of tetany and neuromuscular blockade; (3) changes in cerebral [Ca2+]o caused by hypo- and hyper-calcaemia, and the changes in cerebral [Ca2+]o and pHo caused by acute systemic acidosis and alkalosis; and (4) effects of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The evaluation of the CSP and ICI seen with paired-pulse stimulation reflects complementary approaches for the evaluation of inhibitory mechanisms on the cortical level (10,25). It has been argued that HV increases excitability of spinal motoneurons (26) and motor axons (21,23,28). However, the HV-induced changes in CSP and ICI, seen in the present study, provide good evidence that HV has also distinct effects on neuronal excitability at the cortical level.…”
Section: Ici and Icfsupporting
confidence: 54%
See 2 more Smart Citations
“…The evaluation of the CSP and ICI seen with paired-pulse stimulation reflects complementary approaches for the evaluation of inhibitory mechanisms on the cortical level (10,25). It has been argued that HV increases excitability of spinal motoneurons (26) and motor axons (21,23,28). However, the HV-induced changes in CSP and ICI, seen in the present study, provide good evidence that HV has also distinct effects on neuronal excitability at the cortical level.…”
Section: Ici and Icfsupporting
confidence: 54%
“…HV is known to have various effects on human physiology (for a review, see Ref. 6).For instance, a reduction in Pa CO 2 increases the excitability of sensory and motor axons in the peripheral nervous system (21,23,28).The aim of the present study was to investigate further the neural mechanisms of the HV-induced changes in cortical excitability. As measures of primary motor cortex (M1) excitability, motor threshold (MT), stimulus-response (S-R) curves (i.e., recruitment curves), intracortical inhibition (ICI), and intracortical facilitation (ICF) were determined.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Whereas early studies suggested that hypocapnic voluntary hyperventilation might cause hypocalcemia, modern analysis techniques show that such hypocapnia produces either no hypocalcemia (6,32,48) or too small a reduction to explain adequately any ECG changes, paresthesia, or tetany (14,52).…”
Section: Discussionmentioning
confidence: 99%
“…The NaCl solutions contained 151-136 mM-NaCl and the artificial CSF solutions contained 121-106 mM-NaCl, 22-6 mM-NaHCO3, 3-6 mM-KCl, 1-2 mMMgSO4.7H20, 01 mM-NaH2PO4 and 04 mM-Na2HPO4, pH 7-2-7-4 (Bass & Lundborg, 1973). Calibration in artificial CSF gave a reduction in apparent [Ca2+], presumably the result of calcium ions complexing with bicarbonate and phosphate (Somjen et al 1987 (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%